The history and memory of discrimination in the domain of French nationality: The case of Jews and Algerian Muslims - Weil, Patrick (Hagar: Studies in Society and Culture, 2005)
Since the Republican Regime was definitively installed in France (1875), four categories of French nationals have been subject to discrimination inscribed in nationality law: French women who married foreigners, Algerian Muslims, naturalized citizens and Jews. Although the Republic recognized them as French, they did not always have rights equal to other French nationals. Today such discrimination has disappeared, yet two of these groups - the Jews and the Algerian Muslims - preserve the trace, the memory, the suffering and the lived experience of past discrimination, despite reestablishment of their rights and sometimes recognition or reparation for their loss. This article attempts to understand why. In these two cases, a second event — the discourse of de Gaulle in 1967 and the reform of nationality laws in 1993 — reactivated the painful past and provoked disidentification. This second event occurred during a time of formal equality of rights, and yet harked back to the time of discrimination.